Medical student participation in a surgical outpatient clinic: a randomized controlled trial. Issue 6 (26th March 2013) - Azher, Hinna; Lay, Jennifer; Stupart, Douglas A.; Guest, Glenn D.; Watters, David A. K.
Abstract Background To determine the patient, doctor and student perceptions with different styles of student participation in a surgical outpatient clinic. Methods A randomized controlled trial was conducted in surgical outpatients. Participants included patients scheduled to see one of four specialist general surgeons, the surgeons themselves and third‐year medical students undertaking their general surgery rotation at the Geelong Hospital. A total of 151 consultations were randomized to one of three consultation styles between August 2011 and August 2012. (i) 'No Student', consultation without a student being present, (ii) 'Student with Doctor', consultation where the student accompanied the doctor throughout the consultation and (iii) 'Student before Doctor', consultation where the student interviewed the patient before the doctor and examined the patient in the doctor's presence. Participants' perceptions and experience of each of the consultations was assessed in the form of written questionnaires. Results There was no difference in overall patient satisfaction with different styles of student participation (P = 0.080). Students showed a clear preference for the 'Student before Doctor' consultation style (P = 0.023). There were no differences in consultation outcomes from the doctor's perspective (P = 0.88), except time (P < 0.0001). Conclusion This study supports a style of consultation where students are actively involved in patient care as it has no adverse effects on patient satisfaction and it is the preferred participation style from the student's perspective. Doctors do not feel that active student involvement interferes with their ability to deliver healthcare except that it prolongs consultation time.